Effect of serial photodynamic therapy with curcumin on Leishmania braziliensis and Leishmania amazonensis promastigotes (Research, Society and Development, 2021)
Photodynamic Therapy (PDT) consists of using a light source and a photosensitive drug at an appropriate wavelength and molecular oxygen to trigger cell death through the production of reactive oxygen species. Because it is a localised therapy, PDT is shown to be ideal for skin diseases. American cutaneous Leishmaniasis (ACL) is a highly prevalent protozoan disease worldwide that presents different clinical evolutions and may result in ulcerations and disfiguring lesions on the skin and cartilage. This study was aimed at evaluating the effect in vitro of PDT applied serially using curcumin as a photosensitiser. For this, a concentration of 125 µg.mL-1 of curcumin was used on Leishmania braziliensis and Leishmania amazonensis strains, with a light fluence of 10 J.cm-2 and irradiance of 110 mW.cm-2. The tests done were viability analysis by trypan blue exclusion test, analysis of photosensitizer (PS) internalization by confocal microscopy and morphological alterations by May-Grunwald/Giemsa staining. We observed that there was internalisation of the PS before the first and second application of PDT, with L. braziliensis and L. amazonensis strains mortality of 92% and 82% respectively, after the second application, and induction of alterations in the structural conformation, such as cell size and non-evidence of nucleus and flagellum, demonstrating that PDT was effective. We conclude that serial PDT was effective in inducing the mortality of promastigotes forms of L. braziliensis and L. amazonensis in vitro, thus highlighting its potential for the treatment of leishmaniasis.